Non-Hodgkin's Plasmablastic Lymphoma as Initial Presentation of Human Immunodeficiency Virus. (May 2021) - Jariwal, Roopam; Raza, Nadia; Bhandohal, Janpreet; Cobos, Everardo
Plasmablastic lymphoma (PBL) is a subtype of non-Hodgkin's lymphoma that manifests in patients with the diagnosis of human immunodeficiency virus (HIV), more prominently in the head, neck, and oral mucosal region. The diagnosis of this rare lymphoma serves as a concomitant diagnosis of acquired immunodeficiency syndrome. The case is of a 33-year-old previously healthy male, with an unknown diagnosis of HIV with a painful right mandibular mass. He was subsequently diagnosed with PBL and HIV. This case of PBL illustrates the importance of linking a rare and potentially life-threatening diagnosis as a possible first manifestation of HIV.